Polymer fiber-based models of connective tissue repair and healing. (January 2017) - Lee, Nancy M.; Erisken, Cevat; Iskratsch, Thomas; Sheetz, Michael; Levine, William N.; Lu, Helen H.
Abstract: Physiologically relevant models of wound healing are essential for understanding the biology of connective tissue repair and healing. They can also be used to identify key cellular processes and matrix characteristics critical for the design of soft tissue grafts. Modeling the various stages of repair post tendon injury, polymer meshes of varying fiber diameter (nano-1 (390 nm) < nano-2 (740 nm) < micro (1420 nm)) were produced. Alignment was also introduced in the nano-2 group to model matrix undergoing biological healing rather than scar formation. The response of human tendon fibroblasts on these model substrates were evaluated over time as a function of fiber diameter and alignment. It was observed that the repair models of unaligned nanoscale fibers enhanced cell growth and collagen synthesis, while these outcomes were significantly reduced in the mature repair model consisting of unaligned micron-sized fibers. Organization of paxillin and actin on unaligned meshes was enhanced on micro- compared to nano-sized fibers, while the expression and activity of RhoA and Rac1 were greater on nanofibers. In contrast, aligned nanofibers promoted early cell organization, while reducing excessive cell growth and collagen production in the long term. These results show that the early-stage repair model of unaligned nanoscale fibers elicits a response characteristic of the proliferative phase of wound repair, while the more mature model consisting of unaligned micron-sized fibers is more representative of the remodeling phase by supporting cell organization while suppressing growth and biosynthesis. Interestingly, introduction of fiber alignment in the nanofiber model alters fibroblast response from repair to healing, implicating matrix alignment as a critical design factor for circumventing scar formation and promoting biological healing of soft tissue injuries.